2016
DOI: 10.4238/gmr.15028639
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of association between EPHX1 and chronic obstructive pulmonary disease on the basis of combined data mining

Abstract: ABSTRACT. Chronic obstructive pulmonary disease (COPD) is an important respiratory disease with high mortality. Although smoking is the major environmental risk factor for the development of COPD, only 10% of heavy smokers develop symptomatic disease, suggesting association between genetic susceptibilities and environmental influences. In recent years, as one of the most widely studied genes including tests for associations between a genetic variant and COPD, epoxide hydrolase 1 (EPHX1) was found to be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…However, in the case of Caucasians, we did not identify any statistically significant associations. In contrast, studies of An L found that EPHX1 rs2234922 is not associated with COPD pathogenesis (OR = 1.01, P Z = 0.65) ( An et al, 2016b ). Lee J et al concluded that although a statistically significant correlation was not observed, the presence of EPHX1 rs2234922 correlated with reduced COPD risk, consistent with the theory that the GA genotype of EPHX1 can increase the detoxification ability of the EPHX1 enzyme ( Lee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in the case of Caucasians, we did not identify any statistically significant associations. In contrast, studies of An L found that EPHX1 rs2234922 is not associated with COPD pathogenesis (OR = 1.01, P Z = 0.65) ( An et al, 2016b ). Lee J et al concluded that although a statistically significant correlation was not observed, the presence of EPHX1 rs2234922 correlated with reduced COPD risk, consistent with the theory that the GA genotype of EPHX1 can increase the detoxification ability of the EPHX1 enzyme ( Lee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with the observations that EPHX1 rs1051740 mutations decrease EPHX1 enzyme activity leading to an increase in the risk of COPD. A previous meta-analysis of 19 studies published in 2016 by An L et al did not find any association between EPHX1 rs1051740 and COPD risk in Asians (OR = 0.92, P Z= 0.31) and Caucasians (OR = 1.01, P Z= 0.65) ( An et al, 2016b ). However, this study only used the allele model to pool analysis, which has greater limitations and needs further in-depth mining and research.…”
Section: Discussionmentioning
confidence: 98%
“…There is therefore a growing interest for scientists to extract automatically relevant information from these texts. Several informatics tools have been developed for gene interaction (Mallory et al ., 2016), gene-disease (An et al ., 2016), disease-drug (Bravo et al ., 2015) extraction from scientific and medical texts. Several community challenges for text-mining in biology have been organized to cross-evaluate these tools (Krallinger et al ., 2008; Ananiadou et al ., 2015; Huang and Lu, 2016).…”
Section: Introductionmentioning
confidence: 99%